Hubungan Minat Baca Dengan Hasil Belajar Bahasa Indonesia Siswa Kelas V SD Negeri 1 Lepar Pongok Tahun Ajaran 2019/2020 - Asyraf Suryadin; Erizal Erizal; Romadon Romadon (Pedir Research Institut, 2021)
This research was to find out the relationship between reading interest and Indonesian learning outcomes of grade V students of SD Negeri 1 Lepar Pongok in the academic year 2019/2020 which aimed to find out and to describe whether there is a relationship between reading interest and the students' learning outcomes in Indonesian. This type of research is a correlation research with a quantitative approach. The population in this study was the grade V students of SD Negeri 1 Lepar Pongok, consist of 20 students and the entire population was sampled of the research. The techniques of collecting the datain this study were a questionnaire consisting of 20 statements with the data analysis techniques using the product moment formula. Based on the calculation and the analysis of the data obtained by rcount of 0.946 and rtable of 0.444 so that Ha accepted. It can be conclude that there is a relationship between reading interest with learning outcomes of Indonesian for grade V students of SD Negeri 1 Lepar Pongok. The higher of the students’ interest in reading, the higher of the students’ learning outcomes.